A study of coagulating protein of Moringa oleifera in microalgae bio-flocculation. (September 2016) - Abdul Hamid, Siti Hajar; Lananan, Fathurrahman; Khatoon, Helena; Jusoh, Ahmad; Endut, Azizah
Abstract: Moringa oleifera is characterized by high coagulation properties, low cost and low toxicity hence is very promising to be utilized as an alternative coagulant to recover microalgae biomass from its suspension system. Hence, this study was performed with the objective to investigate the potentiality of M . oleifera as coagulant agent in harvesting microalgae and to investigate the effect of zeta potential in its coagulation-flocculation activity. Bradford protein assay was applied for rapid and accurate determination of protein concentration in the M . oleifera seed powder and protein powder. The flocculation activities were determined at isoelectric pH by computing the flocculation efficiency in terms of microalgae biomass recovery and removal percentage at various coagulant dosages. It was observed that the protein concentration was 211.71 μg g −1  mL −1 in M . oleifera seed powder and 188.16 μg g −1  mL −1 in protein powder which yielded 97% and 78% of biomass recovery, respectively at the dosage of 10 mg L −1 . Result showed that M . oleifera seed derivatives supersede chemical coagulant, alum which yielded 34% of biomass recovery at the same dosage. M . oleifera seed powder and protein powder was proven to be highly promising bio-coagulant and suitable alternative to the chemical coagulant in environmentally-sustainable harvesting of microalgae biomass. Graphical abstract: Highlights: Freshwater Chlorella sp. was selected as microalgae biomass of interest. Flocculation activity of Moringa oleifera seed and alum were tested at various dosage and mixing rate. Optimum flocculation mixing rate was found at 20 rpm with the dosage of 10 mg L −1 . Flocculation assay were performed at isoelectric pH by analyzing zeta potential value. M . oleifera seed powder showed 97% biomass removal as compared to 34% of alum as control.